Pengembangan Modul Berbasis Elektronik Pada Keterampilan Membaca Permulaan Peserta Didik Kelas 1 SD/MI - Amaliyah, Nurrohmatul; Pramasti, Indri (Jayapangus Press, 2024)
Reading is one of the language skills and must be mastered by students. The ability to read is carried out through the initial reading stage which is taught at the 1st grade level of SD/MI. The development of the Modul elektronike for early reading is an innovation in early reading learning in the era of 21st century learning. This development research aims to develop an Modul elektronike for early reading learning for students in grade 1 SD/MI and determine the feasibility of the modul elektronike. The method used in this research is research and development method. The development model used in this study uses the RnD model ADDIE model (Analyze, Design, Develop, Implement and Evaluate). The research and development (RnD) procedure describes the steps that researchers will take in developing a product. The results of the study are (1) the product developed in the form of an Modul elektronike of early reading for grade 1 MI/SD students, the material contained in the module refers to the theory of the early reading stages (2) the results of the validity test by material experts obtained a percentage score of 93% with category is very valid and feasible to use. A media expert percentage score of 80% with a valid category based on conversion means that it is feasible to use. Meanwhile, the results of module trials conducted by students and teachers respectively obtained a score percentage of 95% and 88%, which based on the conversion of the module was feasible to use. With the results of the development of this modul elektronike, it is hoped that it will facilitate and be put to good use by teachers in the learning process for early reading in grade 1 MI/SD.